Footwear and Falls in the Home Among Older Individuals in the MOBILIZE Boston Study - Kelsey, Jennifer L. (2010)
BACKGROUND: Whether certain types of footwear, such as slippers, socks without shoes, and going barefoot, increase the risk for falls among the elderly is uncertain. Our purpose was to examine the relationship between footwear and falls within the home in MOBILIZE Boston, a prospective cohort study of falls etiology among non-institutionalized women and men, mainly aged 70 years and older, from the Boston MA, USA area. METHODS: The 765 participants were from households randomly selected from town lists. They were followed for a median of 27.5 months. At baseline, participants were administered a questionnaire that included questions on footwear usually worn, and were given a comprehensive examination that included measurement of many risk factors for falls. During follow-up participants were asked to record each day whether they had fallen; those reporting falls were asked about their footwear when they fell. RESULTS: At the time of in-home falls, 51.9% of people were barefoot, wearing socks without shoes, or wearing slippers; 10.1% of people reported that their usual footwear was one of these types. Among those who fell in their own home, the adjusted odds ratio for a serious injury among those who were shoeless or wearing slippers compared to those who were wearing other shoes at the time of the fall was 2.27 (95% confidence interval 1.21–4.24). CONCLUSIONS: It may be advisable for older individuals to wear shoes in their home whenever possible to minimize the risk of falling. Further research is needed to identify optimal footwear for falls prevention.